Tiktok Live dan Citra Politik: Studi Kasus Anies Bubble pada Citra Politik Anies Baswedan - Fikri Alkausar; Luthfi Sulistyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
TikTok Live is one of the top features of TikTok social media in user services. The widespread use of TikTok Live and young people who use social media are utilized by one of the candidates for President of the Republic of Indonesia, Anies Baswedan, in the General Election for President of the Republic of Indonesia in 2024. Anies Baswedan in the campaign conducted TikTok Live (28/12/2023) to attract young voters in the closest way to the daily activities of young people. Interestingly, Anies Baswedan's TikTok Live was responded organically with an account on social media X, Anies Bubble (30/12/2024), which refers to Anies and Bubble. Bubble refers to an application used by K-Pop fans to interact with their K-Pop Idols. The emergence of the X social media account @Aniesbubble is an effect resulting from the use of social media that benefits Anies Baswedan's image. Anies Baswedan's previous political image (during the 2017 DKI Jakarta Election) was “haunted” by the image of identity politics, which slowly changed after various campaign activities, one of which was live broadcasting through the TikTok application, especially for young voters.The occurrence of a change in the political image of Anies Baswedan during the General Election of the President of the Republic of Indonesia in 2024 through the campaign carried out, one of which is through the X @AniesBubble social media account.